2001
DOI: 10.1111/j.1469-7793.2001.0143g.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of rat erg1, erg2, erg3 and HERG K+ currents by thyrotropin‐releasing hormone in anterior pituitary cells via the native signal cascade

Abstract: Native ether-à-go-go-related gene (erg) K + currents were first described in sinoatrial node cells as delayed rectifier K + current. This current exhibited clear inward rectification in the 'fully activated' current-voltage relationship (DiFrancesco et al. 1979) and this property was explained by a channel model with two independent gates: a fast inactivation gate and a slow activation gate (Shibasaki, 1987 1. The mechanism of thyrotropin-releasing hormone (TRH)-induced ether-à-go-go-related gene (erg) K + cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
115
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(141 citation statements)
references
References 53 publications
(110 reference statements)
22
115
3
Order By: Relevance
“…The sustained membrane hyperpolarization and decrease in input resistance observed in ET-1-stimulated cells indicate that ET A receptors activate or augment a hyperpolarizing current rather than inhibit a depolarizing Pituitary lactotrophs express two channel subtypes that are sensitive to Cs ϩ at the concentrations used in our experiments, K ir and erg-like channels, but only the latter is also sensitive to E-4031 (Einhorn et al, 1991;Schafer et al, 1999;Schledermann et al, 2001). Initiation of [Ca 2ϩ ] i transients in quiescent lactotrophs and the increase in the frequency of [Ca 2ϩ ] i transients in spontaneously active cells after the addition of 5 mM Cs ϩ and 1 M E-4031 are consistent with the role of erg-like channels in controlling the firing frequency in unstimulated cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The sustained membrane hyperpolarization and decrease in input resistance observed in ET-1-stimulated cells indicate that ET A receptors activate or augment a hyperpolarizing current rather than inhibit a depolarizing Pituitary lactotrophs express two channel subtypes that are sensitive to Cs ϩ at the concentrations used in our experiments, K ir and erg-like channels, but only the latter is also sensitive to E-4031 (Einhorn et al, 1991;Schafer et al, 1999;Schledermann et al, 2001). Initiation of [Ca 2ϩ ] i transients in quiescent lactotrophs and the increase in the frequency of [Ca 2ϩ ] i transients in spontaneously active cells after the addition of 5 mM Cs ϩ and 1 M E-4031 are consistent with the role of erg-like channels in controlling the firing frequency in unstimulated cells.…”
Section: Discussionmentioning
confidence: 96%
“…Two channels expressed in pituitary lactotrophs could mediate the ET-1-induced and Cs ϩ -sensitive hyperpolarizing current: K ir channels (Einhorn et al, 1991;Kuryshev et al, 1997) and/or ether-a go-go-related gene (erg)-like K ϩ channels (Schafer et al, 1999;Schledermann et al, 2001). Both channels are activated by hyperpolarizing pulses, exhibit inward rectification, and can be blocked by Cs ϩ .…”
Section: Characterization Of Kmentioning
confidence: 99%
“…However, it should be noted that the studies based on the usefulness of HERG current are limited owing to the non-native conditions (e.g., α-subunits) of the ion channel in Xenopus oocytes or in the host HEK293 cells. Moreover, GH 3 cells used in this study were reported to contain many different isoforms of endogenous erg channels (10,13). The issues of whether other isoforms of erg channels are subject to more sensitive to block by ranolazine remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…1B). For rERG3, in the region from Ϫ40 to ϩ40 mV, a shift to the right has been reported (Schledermann et al, 2001;Sturm et al, 2005) with respect to rERG1 and rERG2. Our data, obtained with the use of a different method (see inset and Materials and Methods) in a much larger voltage range from Ϫ160 to ϩ20 mV, did not evidence this effect.…”
Section: Erg Channels and Erg Toxins 1675mentioning
confidence: 99%